Analisis Willingness to Pay Pengunjung dan Peningkatan Sarana Prasarana Objek Wisata Grand Maerokoco di Kota Semarang - Aiman Qowi; Fitrie Arianti (Diponegoro Journal of Economics, 2020)
This study aims to look at the socio - economic characteristics of Grand Maerokoco visitors, see tourist perceptions of Grand Maerokoco Tourism Objects, measure willingness to pay of tourists, and identify strategies for development Grand Maerokoco Attractions in Semarang City. This study used Mix Methods Method, a combination of quantitative and qualitative approaches applied to analyze data. Descriptive statistics are used to analyze numerical data of socio - economic characteristics, tourist perceptions, and also the offer value of the average willingness to pay tourists. The results of this study indicate that the condition of the grand Maerokoco Tourism Object through the interview there are enough facilities but still need a lot of improvement according to the visitors interviewed. The Contingent Valuation Methods results found 93% of the total respondents who were willing to pay the Willingness to Pay offer value, so that the average WTP value of Rp 14.000 was obtained with a total WTP value of Rp 589.610.000.